2015
DOI: 10.1128/jvi.01048-15
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome (SARS) Coronavirus ORF8 Protein Is Acquired from SARS-Related Coronavirus from Greater Horseshoe Bats through Recombination

Abstract: IMPORTANCEAlthough horseshoe bats are the primary reservoir of SARS-related coronaviruses (SARSr-CoVs), it is still unclear how these bat viruses have evolved to cross the species barrier to infect civets and humans. Most human SARS-CoV epidemic strains contain a signature 29-nucleotide deletion in ORF8, compared to civet SARSr-CoVs, suggesting that ORF8 may be important for interspecies transmission. However, the origin of SARS-CoV ORF8 remains obscure. In particular, SARSr-Rs-BatCoVs from Chinese horseshoe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
192
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(209 citation statements)
references
References 70 publications
14
192
3
Order By: Relevance
“…Numbers indicate bootstrap support. CoVs are colored according to [14,15]. Analysis of the ORF8 region revealed high sequence identity with civet/human SARS-CoV.…”
Section: Box 1 Molecular Evolution In Viruses: General Conceptsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numbers indicate bootstrap support. CoVs are colored according to [14,15]. Analysis of the ORF8 region revealed high sequence identity with civet/human SARS-CoV.…”
Section: Box 1 Molecular Evolution In Viruses: General Conceptsmentioning
confidence: 99%
“…Analysis of the ORF8 region revealed high sequence identity with civet/human SARS-CoV. Two groups came to the conclusion that recombination within SARSr-Rs-CoVs or between SARSr-Rs-CoVs and SARSr-Rf-CoVs led to the acquisition of an ORF8 closely related to that of civet/human SARS-CoV and ultimately originated the virus responsible for the human epidemic [14,15]. Interestingly, Lau and coworkers also reported that the ORF8 region has a dN/ dS = 3.5 in SARS-CoVs isolated from humans (but not in SARSr-BatCoVs), indicating the action of positive selection (Box 1) [14].…”
Section: Box 1 Molecular Evolution In Viruses: General Conceptsmentioning
confidence: 99%
See 3 more Smart Citations